The influencing power of social presence and social support towards trust on social commerce during national recovery plan - Lai, Tze Wee (2022)
Social commerce is a new advancement of ecommerce that merges the commercial and social activities by deploying social technologies into e commerce reintrodu ces e-- commerce sites. Social commerce from the perspective of social media networks. The findings demonstrate the validity of three dimensions of social presence: social presence of online brand community, social presence of others, and social presence of interaction; and two di mensions of social support: informational support and emotional support. This study consisted of one hundred and eighty respondents from Malaysia Facebook shoppers aged 18 and above have participated in this quantitative study using convenience sampling. A questionnaire that contained twenty items was used as a tool for data collection using the survey method. Our findings indicate that all factors in social presence and social support had a significant relationship with trust in social commerce, except for emotional support. Theoretically, these findings contribute to a better understanding of the effect of social presence and social support on consumers’ trusting beliefs in social commerce. Finally, theoretical and managerial implications for nurturing thr iving businesses in social commerce environment along with limitations and directions for future research have also been provided. This research introduces a new perspective of ecommerce and calls more attention to this new phenomenon of social commerce.